Developing a novel in-situ polymerisation process for fully bioresorbable fibre reinforced composites - Menghao, Chen (2018)
In recent decades, fully bioresorbable polymer composites with appropriate biocompatibility and mechanical properties have provided an exciting opportunity to replace conventional metal alloy implants. This work explores the development of a novel, one-step in-situ polymerisation (ISP) process for the manufacture of fully bioresorbable phosphate based glass fibre (PGF) reinforced composites with matrix materials of polycaprolactone (PCL), polycaprolactone-polylactic acid copolymer (PLA-PCL) and polylactic acid (PLA). Composites produced via conventional laminate stacking (LS) process were used as the comparison to demonstrate the advantages that ISP can provide in composites quality. In-vitro degradation in phosphate buffered saline (PBS) at 37 °C, flexural property retention and cytocompatibility were investigated for both LS and ISP composites. Additionally, the composites were degraded under representative flexural loading for high cycle fatigue analysis to understand and predict their lifetime in service and their likely mechanisms of failure. Significantly more robust fibre/matrix interface and uniform fibre distribution along the cross section of the composites were achieved via ISP compared to LS. These enhancements resulted in considerably higher initial mechanical properties (~450 MPa and ~24 GPa for flexural strength and modulus, close to the upper range of human cortical bone properties), prolonged mechanical retention, less and slower water uptake and mass loss profiles for the ISP composites. The flexural fatigue life of the ISP composites was at least 10 times longer than the LS composites counterpart within both dry and wet (within PBS at 37 °C) testing environments. Furthermore, positive cytocompatibility was also found for both the LS and ISP PLA/PGF composites. Conclusively, ISP composites exhibited considerably enhanced mechanical retention and drastically improved media resistance, making those fully bioresorbable composites significantly more favourable as materials for bioresorbable bone fracture fixation devices.